Fluorescence Properties of Hydrophilic Semiconductor Nanoparticles with Tridentate Polyethylene Oxide Ligands - Thiry, Marc; Boldt, Klaus; Nikolic, Marija S.; Schulz, Florian; Ijeh, Michael; Panicker, Andjana; Vossmeyer, Tobias; Weller, Horst (My University, 2011)
In this contribution a facile, one-step synthesis of tridentate thiol-functionalized PEO ligands and their ability to stabilize CdSe/CdS/ZnS core-shell-shell nanoparticles in aqueous media are described. The PEO-coated quantum dots show colloidal stability as well as preserved fluorescence even at very low concentrations of a few nM. For improved ligand attachment and enhanced fluorescence properties a method for ligand exchange was developed, which includes formation of a ligand zinc complex before the actual exchange reaction. The stability and fluorescence properties in various aqueous buffers and cell media and at pH values down to pH 3 were investigated. The firm binding of the tridentate ligands to the particle surface makes this ligand-particle system a promising tool for biological applications. In addition, activation of the ligands' terminal hydroxyl group for covalent biofunctionalization by esterification with succinic acid is reported.
Keywords: CdSe/CdS/ZnS; ligands; photoluminescence; poly(ethylene glycol); polyethylene oxide; quantum dots; water-soluble; 540